(untitled) (International Academic Research Journal of Business and Management, 2015)
Today everyone needs to advertise their products to inform the customers about the product, increase the sales, acquire market share, and attain top position in their respective industry. Every business spends lot of money for advertising their products but the money spent will lead to success only when the best techniques of advertising are used for the product. In recent years, advertising has witnessed a significant transformation in attracting customer to buy/use their products/services. The need for advertisements has risen to great levels in print and visualmedia. One among the transformation is the way women are depicted in advertising, with changing times, reflecting the transformation taking place in society. Advertising is one of the major media that affect our daily life consciously and unconsciously and are responsible to play a significant role in shaping the society in a much broader perspective. Women today are no longer consolidated behind kitchen walls. Their aspiration for stepping out in the world made society to think differently. Marketer wisely utilized this transformation process to launch their product and advertisement strategically. This paper is a part of research work and the report will seek to define the portrayal of women in advertisements and its effect on cultural values. Survey research method is used for the analysis on the basis of gender and age. The literature review indicates that the women are portrayed mainly as an object of attraction. The results argue that the portrayal in advertising is changing the concept of respect about women, spreading uncultured values and also indicate women's physical beauty as an instrument to induce the products demands.